Chapter 5.15 Research Management and Administration (RMA) in Singapore: Development of RMA Capability in Nanyang Technological University (NTU) - Alana M. Soehartono; Khiam Aik Khor (Emerald Publishing Limited, 2023)
Singapore's research has grown significantly since the first national R&D plan was launched in 1991, the same year Nanyang Technological University (NTU) was established. NTU's research progression, vitally funded by the government, mirrored the substantial growth of Singapore's research. NTU began as an engineering-based higher education institution that also had a school for accountancy and business, but more schools were added after 2000. Since then, the university has established a research ecosystem that includes research centres of excellence, corporate labs, and medium-sized research centres. Concurrently, the development of research administration in NTU has evolved from providing pre- and post-award support, extending to include outreach, research integrity and ethics, bibliometrics analysis, and talent recruitment and career support. The evolution of administrative needs and capabilities following the changing environment underscores the dynamic nature of research management and administration in Singapore.
10.1108/978-1-80382-701-820231049; 10.1108/978-1-80382-701-820231049; The Emerald Handbook of Research Management and Administration Around the World; EBP099697262